Pivoting during a Pandemic: Reimagining Intern Orientation EPA-Based OSCE. Issue 3 (March 2023) - Suneja, Manish; Thoma, Kate DuChene; Franklin, Ellen; Rowat, Jane
Abstract : Objective structured clinical examinations (OSCEs) provide reliable and standardized means for assessing the performance of core clinical skills. Our previous experience with entrustable professional activity-based multidisciplinary OSCEs suggests that this exercise offers just-in-time baseline information regarding critical intern skills. The coronavirus disease 2019 pandemic forced medical education programs to reimagine such educational experiences. For the safety of all of the participants, the Internal Medicine and Family Medicine residency programs pivoted from an in-person OSCE to a hybrid model (combination of in-person and virtual encounters) while maintaining the goals of the OSCE administered in previous years. This article describes an innovative pivot to redesign and implement a previous in-person OSCE to a hybrid OSCE model for interns without compromising intern clinical skills assessment or satisfaction of intern residents and faculty observers. Abstract: Objectives: Objective structured clinical examinations (OSCEs) provide reliable and standardized means for assessing the performance of specific clinical skills. Our previous experience with entrustable professional activity-based multidisciplinary OSCEs suggests that this exercise offers just-in-time baseline information regarding critical intern skills. The coronavirus disease 2019 pandemic forced medical education programs to reimagine such educational experiences. For the safety of all of the participants, the Internal Medicine and Family Medicine residency programs pivoted from an in-person OSCE to a hybrid model (combination of in-person and virtual encounters) while maintaining the goals of the OSCEs administered in previous years. Here, we describe an innovative hybrid approach to redesigning and implementing the existing OSCE model while maximizing risk mitigation. Methods: In total, 41 interns from Internal Medicine and Family Medicine participated in the 2020 hybrid OSCE. Five stations allowed for clinical skills assessment. Faculty completed skills checklists with global assessments and simulated patients completed communication checklists with global assessments. Interns, faculty, and simulated patients completed a post-OSCE survey. Results: Informed consent, handoffs, and oral presentation were the lowest performing stations (29.2%, 53.6%, 53.6%, respectively) as assessed by faculty skill checklists. One hundred percent of interns (41/41) indicated that immediate faculty feedback was the most valuable part of the exercise, and all of the participating faculty believed that the format was efficient, allowing ample time to provide feedback and complete checklists. Eighty-nine percent of simulated patients cited they would be willing to participate again if the same assessment were to be held during the pandemic. The limitations of the study included the lack of demonstration of physical examination maneuvers by interns. Conclusions: A hybrid OSCE to assess interns' baseline skills during orientation using Zoom technology could be delivered successfully and safely during the pandemic without compromising the program's goals or satisfaction.